Renewable Energy Products and Customer’s Purchase Intentions having Environmental Concern - Malik, Muhammad Imran; Ahmad, Mubashir; Hussain, Arif; Saleem, Farida; Durrani, Muhammad Kashif; Hyder, Shabir; Qureshi, Saiqa Saddiqa; Imtiaz, Shoaib; Malik, Shumaila (International Journal of Energy Economics and Policy, 2020)
The wind or solar, a renewable energy source, is not depleted when used. The current study examined the relationship of renewable energy products (solar panels and related equipment) and customer purchase intentions with a mediating role of customer’s concern for the environment and perceived risk involved in buying such products. A cross-sectional, quantitative, and explanatory design is used by sampling 354 male and female customers on convenience basis. Structural equation modeling is applied through AMOS software for hypotheses testing. The results revealed that customers product related knowledge, environmental concern and even risk involved helped customers develop their purchase intentions regarding purchase of renewable energy products. This study used a cross-sectional design and used a single segment of products that are solar panels (renewable energy technology/product). It is recommended that future studies must use other research designs with diverse samples and products. Single aspect of risk is used in the study that was physical risk related to product other types of risk may bring interesting insights. The effort is made to know the customer intentions for purchasing renewable energy products for environmental protection. Greater the knowledge higher will be the propensity of developing purchase intentions. Marketers must focus on reducing risks and enhance confidence by educating them for increased purchase intentions, particularly when it is about renewable energy products. The study examined the linkages between knowledge, risk and environmental concern shaping the purchase intentions that have not been examined earlier in the context of energy deficient country – Pakistan and highlighted the need for renewable energy use. Keywords: customer; knowledge; renewable energy products; physical risk; environmental concern; purchase intentions. JEL Classifications: M31, M37 DOI: https://doi.org/10.32479/ijeep.10427